Breed-related differences in age-dependent down-regulation of the β1-adrenoceptor and adenylate cyclase activity in atrial and ventricular myocardium of Cröllwitzer ("wild-type") turkeys. (13th December 2017) - Hoffmann, Sandra; Böhme, Julia; Kube, Christian; Pees, Michael; Haufe, Jörg; Abraham, Getu
Abstract: In conventional meat-type (British United Turkey (B.U.T.) Big 6) turkey hearts, it has been shown that all cardiac chambers exhibit down-regulation of the β1 -adrenoceptors (β1 -AR) and concomitantly cAMP accumulation with increasing age regardless of sex. In this study we proved the hypothesis that breed differences exist in age-dependent alterations in the β1 -AR system. Right (RA) and left (LA) atrial as well as right (RV) and left (LV) ventricular tissues were collected from male and female Cröllwitzer "wild-type" turkey poults of increasing age (6 wk, 12 wk, 16 wk, 21 wk). The β1 -AR density and function were quantified by (-)-[ 125 I]-iodocyanopindolol (ICYP) radioligand binding analysis in cell membranes from 4 cardiac chambers. Basal and stimulated cAMP production was determined as indicator of the receptor function. Wild-type turkeys showed significantly higher heart to body weight ratio than the meat-type B.U.T. Big 6 turkeys. In both sexes of Cröllwitzer turkey hearts, the β1 -AR density decreased with age but significance was reached in male cardiac chambers. The receptor affinity (KD ) and subtype distribution were not altered. Sex had no effect on age-related decrease in receptor density but had an effect on adenylate cyclase (AC) activity and subsequently cAMP production. In male Cröllwitzer turkey hearts of all ages, cAMP remained at same level, whereas this was even increased in female cardiac chambers. Thus, breed affected age-related receptor-, G-protein and AC-stimulated cAMP formation in normal ventricles and atria, with females exhibiting pronounced increase with age. This suggests that the receptor signaling in wild-type turkey hearts is not as blunted as in hearts of meat-type turkey poults in which stressful farming conditions and fast growing lead to receptor down-regulation.